2012 IEEE RO-MAN: The 21st IEEE International Symposium on Robot and Human Interactive Communication 2012
DOI: 10.1109/roman.2012.6343829
|View full text |Cite
|
Sign up to set email alerts
|

Influence of legibility on perceived safety in a virtual human-robot path crossing task

Abstract: Abstract-In the future robots will more and more enter our daily life. If we want to increase their acceptance it is necessary that people feel safe in the surrounding of robots. As a prerequisite we think that the robot's behavior has to be legible in order to achieve such a feeling of perceived safety. With our present experiment we assess the perceived safety participants feel when an autonomous robot is crossing their path in a video based virtual scenario watched in first person perspective. The robot is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 15 publications
3
53
0
Order By: Relevance
“…A robot has to navigate through spaces where humans live and as Althaus et al [1] already stated "The quality of the movements influences strongly the perceived intelligence of the robotic system.". The way a robot moves affects not only the perceived intelligence, also the perceived safety, comfort and legibility and other factors regarding social acceptance [7,17]. Therefore, one goal in human-robot interaction is to develop methods in order to make robot behavior and in particular navigation socially acceptable [16,8,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A robot has to navigate through spaces where humans live and as Althaus et al [1] already stated "The quality of the movements influences strongly the perceived intelligence of the robotic system.". The way a robot moves affects not only the perceived intelligence, also the perceived safety, comfort and legibility and other factors regarding social acceptance [7,17]. Therefore, one goal in human-robot interaction is to develop methods in order to make robot behavior and in particular navigation socially acceptable [16,8,22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, imitating human behavior becomes difficult. Furthermore we showed in former experiments [17] that the legibility and perceived safety of the Human-Aware Navigation method [15] is rather low. In addition, it is not clearly known if humans expect robots to move in a different manner to humans.…”
Section: Introductionmentioning
confidence: 99%
“…A prerequisite for the acceptance of robots in everyday situations is that they move naturally and predictably and that humans feel safe. Several approaches have been proposed to make robot navigation socially acceptable [1]- [3] and Lichtenthäler et al [4] showed in their experiments that the legibility and perceived safety of common navigation methods are rather low. However, there is currently no understanding of what humans expect from the navigation capabilities of a robot, in particular how it should behave in dynamic situations when the paths of humans and robots cross.…”
Section: Introductionmentioning
confidence: 99%
“…The situation can change quickly, obstacles may not be on the map, either because they move themselves (like people or pets or other household robots) or because they are movable (like chairs). Relying too much on path planning in dynamic environments leads to illegible 1 behavior [11,14]. On the positive side, rooms are usually furnished in a way to make navigation easy for people and thus hardly contain dead ends.…”
Section: Motivationmentioning
confidence: 99%
“…It remains to be tested in dynamic environments, which allow for a much higher variance of situations. Typical navigation algorithms such as the ones implemented in ROS behave different in crossing situations than people [11,2] and are not really legible [14].…”
Section: Related Workmentioning
confidence: 99%